Ag+↔Na+ ion exchanged silicate glasses for solar cells covering: Down-shifting properties. Issue 5 (June 2015) - Cattaruzza, E.; Caselli, V.M.; Mardegan, M.; Gonella, F.; Bottaro, G.; Quaranta, A.; Valotto, G.; Enrichi, F.
Abstract: The suitability of the Ag + ↔Na + ion exchange process was tested for the production of luminescent cover glasses with down-shifting properties suitable for solar cells. The photoluminescence properties were investigated as a function of the preparation parameters (i.e., Ag salt bath concentration, post-synthesis annealing temperature and duration). The performance of the samples was tested by measuring the output power of a Si solar cell covered with the treated glass slides and exposed to a solar simulator radiation; the photoluminescence quantum yield of the best performing samples was also estimated.